Integration of food markets in India: A case of milk markets - Kumar, Shiv; Birthal, Pratap S; Chaudhary, Khyali Ram (The Indian Journal of Animal Sciences, 2011)
Dairy policy in India has undergone a sea change in recent years, creating an ample space for public and private investment in dairy business. This is likely to have influenced inter-regional trade in dairy products and prices there of in different markets. This paper examines integration of milk markets, and concludes that milk markets have moved towards a long–run integration after a course of corrections and adjustments. Some markets are more stable due to existence of strong basics of production and marketing in the regions where they are located. However, the less stable markets are also important to sustain long–run equilibrium or to correct disequilibrium due to short-run exogenous shocks.